The Effects of Integrating Mindfulness Exercises into the Elementary Science Curriculum: A Cluster, Randomized, Controlled Trial - Orit Shelach Inbar; Ricardo Tarrasch (Education Sciences)
In the past two decades, there has been an increasing interest in integrating mindfulness practices as part of the school curriculum. The aim of this study was to examine the impact of a unique intervention program, specifically designed for the study, which integrated mindfulness exercises as an integral part of the science curriculum. The study involved 460 students aged 9–11 from six elementary schools. In each school, classes were randomly assigned to either an experimental group or a control group. In the experimental group, science lessons were taught using a contemplative instruction approach that incorporated mindfulness activities, including introspective inquiry, mental training, and meditation, focused on the specific content of each science class. In the control group, science lessons were taught as usual. Students filled in questionnaires and achievements were collected before, immediately after, and six months after the intervention. Students in the mindfulness group demonstrated significantly higher levels of mindfulness, motivation, and achievement in science compared to students in the control group, and the improvement was maintained 6 months later. The program used in this study can be relatively easily integrated into the elementary school curriculum as a whole and specifically in the science discipline.